2014
DOI: 10.1680/macr.13.00096
|View full text |Cite
|
Sign up to set email alerts
|

Critical overview of blast resistance of different concrete types

Abstract: Past attacks against buildings and civil infrastructure highlight the need for blast-resistant structural materials.Numerous studies have been conducted on various related techniques and some design guidance has been developed to increase the resistance of structures to blast loading. Generally, a blast results in a high-amplitude impulse loading typically with a very short duration. Hence, the material's response to such loading will differ from its response to regular types of loading. Consequently, the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Over the last decades, reinforced concrete structures have been subjected to various extreme loading conditions, including impacts, explosions and earthquakes, which instigated several unexpected structural failures. This has escalated the impact load design requirements of concrete structures to mitigate such catastrophic failures [1][2][3]. Accordingly, the dynamic properties of concrete structural elements must be enhanced for better structural safety specifications [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, reinforced concrete structures have been subjected to various extreme loading conditions, including impacts, explosions and earthquakes, which instigated several unexpected structural failures. This has escalated the impact load design requirements of concrete structures to mitigate such catastrophic failures [1][2][3]. Accordingly, the dynamic properties of concrete structural elements must be enhanced for better structural safety specifications [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…A FRP could be used as a strip, wrap or spray in RC structures to increase its blast resistance by enhancing the ductility, shear and flexural capacity [72,73]. Blast damage can be minimized and spall and fragmentation can be completely prevented through AFRP strengthening of RC structures, because this material exhibits a high energy absorption capacity [30]. It is considered that the blast resistances of CFRP-and GFRP-strengthened RC structures are nearly identical, but hybrid aramid/glass fibre composites are more reliable and provide improved flexibilities under blast loadings [72].…”
Section: Blast Resistancementioning
confidence: 99%
“…Around 30% increase in the energy absorption capacity and 85% decrease in the displacement were observed after strengthening a RC panel by using a CFRP sheet under a blast of 15.88 kg explosive charge with 1.5 m standoff distance [75]. Even the post-blast static strength could be improved by up to 70% by FRP strengthening [30]. While designing a strengthening system for provide resistance against blast loading, the bond strength and the requirement of an anchorage system need to be analysed first [74,76].…”
Section: Blast Resistancementioning
confidence: 99%
“…The amplitude of transferred stress was related to the specimen length. Alhadid et al (2014), Edward et al (2012). Analyzed the microstructural characteristics of foam concrete and concluded that the existence of pores makes foam concrete fragile.…”
Section: Introductionmentioning
confidence: 99%